Positive allosteric modulation of the muscarinic M1 receptor improves efficacy of antipsychotics in mouse glutamatergic deficit models of behavior - Choy, Kwok H.C.; Shackleford, David M.; Malone, Daniel T.; Mistry, Shailesh N.; Patil, Rahul T.; Scammells, Peter J.; Langmead, Christopher J.; Pantelis, Christos; Sexton, Patrick M.; Lane, Jonathan R.; Christopoulos, Arthur (American Society for Pharmacology and Experimental Therapeutics, 2016)
Current antipsychotics are effective in treating the positive symptoms associated with schizophrenia, but they remain suboptimal in targeting cognitive dysfunction. Recent studies have suggested that positive allosteric modulation of the M1 muscarinic acetylcholine receptor (mAChR) may provide a novel means of improving cognition. However, very little is known about the potential of combination therapies in extending coverage across schizophrenic symptom domains. This study investigated the effect of the M1 mAChR positive allosteric modulator BQCA [1-(4-methoxybenzyl)-4-oxo-1,4-dihydroquinoline-3-carboxylic acid], alone or in combination with haloperidol (a first-generation antipsychotic), clozapine (a second-generation atypical antipsychotic), or aripiprazole (a third-generation atypical antipsychotic), in reversing deficits in sensorimotor gating and spatial memory induced by the N-methyl-d-aspartate receptor antagonist, MK-801 [(5R,10S)-(+)-5-methyl-10,11-dihydro-5H-dibenzo[a,d]cyclohepten-5,10-imine]. Sensorimotor gating and spatial memory induction are two models that represent aspects of schizophrenia modeled in rodents. In prepulse inhibition (an operational measure of sensorimotor gating), BQCA alone had minimal effects but exhibited different levels of efficacy in reversing MK-801–induced prepulse inhibition disruptions when combined with a subeffective dose of each of the three (currently prescribed) antipsychotics. Furthermore, the combined effect of BQCA and clozapine was absent in M1−/− mice. Interestingly, although BQCA alone had no effect in reversing MK-801–induced memory impairments in a Y-maze spatial test, we observed a reversal upon the combination of BQCA with atypical antipsychotics, but not with haloperidol. These findings provide proof of concept that a judicious combination of existing antipsychotics with a selective M1 mAChR positive allosteric modulator can extend antipsychotic efficacy in glutamatergic deficit models of behavior.